(untitled) (KULT_online, 2010)
In this collection edited by Ingrid Kasten and Erika Fischer-Lichte, the central question is how the medieval religious play can be interpreted in terms of performativity and textuality, two terms thought to facilitate an understanding of the aesthetical transformation of the religious. Focus of the debate is the German religious play. The concepts of performativity and also those of presence and rituality are mostly known as part of a post-dramatist approach to contemporary forms of theatre. Many of these essays prove, however, that such an approach is especially fruitful in the context of medieval cultural forms of expression – even more so than for contemporary theatre.